Operational Efficiency and Financial Health: Analysing Indian Public and Private ‎Banks Using CAMEL Framework and Regression Models - P. , Rose Martina; K., Vinitha (International Journal of Accounting and Economics Studies, 2026)
This study analyzed data on the performance of public sector banks (SBI and BOB) and private sector banks (HDFC Bank and ICICI Bank) from 2018 to 2023 in India. The financial status and performance of banks are crucial for the ‎economy. By using descriptive statistics, important financial ratios, the CAMEL framework, multiple regression analysis, and Efficiency analysis, the study concludes on the major differences and trends. The findings of the study reflect the major ‎improvement in the performance of Private Sector banks, especially HDFC Bank, in respect of ‎efficiency, profitability, asset quality in terms of ROA, ROE, NIM, and NPA ratios. It was ‎also highlighted in the study that few improvements have been made in the performance of ‎public sector banks, but still, they fail to compete in terms of efficiency, profitability, and asset ‎quality with Private Sector banks. Moreover, the study also distinguished that the changes in ‎the macroeconomic variables do impact the bank’s performance. Therefore, the study also ‎indicates the possible additional determinants that can be further investigated. The ‎findings of the study are hence significant for bank managers and policymakers while ‎taking necessary corrective measures and recommendations for the improvement in the ‎financial health and competitiveness of public sector banks. The key recommendation of the ‎study, hence, is to adopt efficient operational and risk management practices.